TRAP OF ECONOMICS THE WORLD HAS FALLEN IN A SURVEY OF KINOSHITA THEORY IN MACROECONOMICS - Eizo Kinoshita; Takafumi Mizuno (European Scientific Journal, ESJ, 2015)
This paper is a survey of Kinoshita’s Macro-Economic theory and new Macro- Economic paradigm. Throughout his study, he proclaims there are two economic phases: one is expressed primal problem, and another is expressed its dual problem. And he states that the two economic phases have duality relations. His theory reaches analysis of global trade, bubble economy and its crash. His main tools for the analysis are linear programing on operations research. We summarize his five published papers which construct his theory and paradigm, and we point out that ignorance of his theory makes the world economy fall in trap of economics.